Marriage dynamics and fertility in the era of HIV and AIDS in Mahikeng Local Municipality of the North West Province, South Africa - Rampagane, Kelebogile Veronica (My University, 2016)
Marriage as one of the proximate determinants of fertility is in transition globally. In South Africa, age at marriage is increasing, marriage rate is declining, the prevalence of cohabitants and marriage dissolution is increasing, and single motherhood is on rise in a country where HIV infection is generalized. On the other hand, marital fertility is declining. The study was therefore premised by the changing marriage patterns and fertility in the context of a generalized HIV and Aids pandemic in South Africa. The main objective of the study was to examine marriage patterns and lifetime fertility in the era of HIV and AIDS in Mahikeng local Municipality, with the view of assessing their dynamics and predictors. The study used cross-sectional data collected from 605 randomly selected women aged 15-49 years of age. Descriptive statistics including the Pearson’s chi-square statistics and the Kaplan-Meier Log rank statistics and inferential statistics including the Cox Proportional Hazards Model and the nested Binary Logistic Regression Model were used in the analysis. The study found that marriage rate was only 33%, the median age at marriage was 24 years and the mean parity of the women was only 1.9. The low marriage rate was significantly predicted by being African, living in the poorer socioeconomic neighbourhood, having tertiary education and work in the formal sector. Early marriage was predicted by rural childhood residence, having no/primary education, work in the informal sector and belonging to the 35 years or older age group. Conversely, use of contraceptives, perceived high risk of HIV infection and living in the poorer socioeconomic neighbourhoods delayed marriage. Furthermore, the lower lifetime fertility was predicted by sexual debut at 18 years or older, never married status, having tertiary education and work in the formal sector. The study concludes that marriage rate in Mahikeng Local Municipality is low among African women; the age at marriage is increasing; and lifetime fertility is declining. Although perceptions of risk of HIV infection appear to impact marriage rate negatively, it appears not to be an important factor in fertility decisions in the study population. Either way, both processes could continue to compounding the HIV and Aids problem. Programmes addressing socioeconomic inequalities through education and employment on one hand and the HIV and Aids pandemic through promoting HIV testing and HIV status disclosure on the other are important and can contribute to improving marriage and fertility behaviour in the study area.
PhD (Population Studies), North-West University, Mafikeng Campus, 2016
Keywords: Marriage; Lifetime fertility; HIV and AIDS; Mahikeng